Highly loaded cellulose/poly (butylene succinate) sustainable composites for woody-like advanced materials application - Platnieks, Oskars; Gaidukovs, Sergejs; Barkane, Anda; Gaidukova, Gerda; Grase, Liga; Thakur, Vijay Kumar; Filipova, Inese; Fridrihsone, Velta; Skute, Marite; Laka, Marianna (MDPI, 2019)
We report the manufacturing and characterization of poly (butylene succinate) (PBS) and micro cellulose (MCC) woody-like composites. These composites can be applied as a sustainable woody-like composite alternative to conventional fossil polymer-based wood-plastic composites (WPC). The PBS/MCC composites were prepared by using a melt blending of 70 wt% of MCC processed from bleached softwood. MCC was modified to enhance dispersion and compatibility by way of carbodiimide (CDI), polyhydroxy amides (PHA), alkyl ester (EST), (3-Aminopropyl) trimethoxysilane (APTMS), maleic acid anhydride (MAH), and polymeric diphenylmethane diisocyanate (PMDI). The addition of filler into PBS led to a 4.5-fold improvement of Young’s modulus E for the MCC composite, in comparison to neat PBS. The 1.6-fold increase of E was obtained for CDI modified composition in comparison to the unmodified MCC composite. At room temperature, the storage modulus E′ was found to improve by almost 4-fold for the APTMS composite. The EST composite showed a pronounced enhancement in viscoelasticity properties due to the introduction of flexible long alkyl chains in comparison to other compositions. The glass transition temperature was directly affected by the composition and its value was −15 °C for PBS, −30 °C for EST, and −10 °C for MAH composites. FTIR indicated the generation of strong bonding between the polymer and cellulose components in the composite. Scanning electron microscopy analysis evidenced the agglomeration of the MCC in the PBS/MCC composites. PMDI, APTMS, and CDI composites were characterized by the uniform dispersion of MCC particles and a decrease of polymer crystallinity. MCC chemical modification induced the enhancement of the thermal stability of MCC composites.
Keywords: cellulose; poly (butylene succinate) composite; physical-mechanical properties; thermo-mechanical properties; sustainable woody-like composites